2006
DOI: 10.1128/aac.50.3.975-983.2006
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Potential for Resistance Selection of Antipseudomonal Treatments in a Mouse Model of Lung Infection by HypermutablePseudomonas aeruginosa

Abstract: Hypermutable Pseudomonas aeruginosa strains are found with high frequency in the lungs of patients with chronic infections and are associated with high antibiotic resistance rates. The in vivo consequences of hypermutation for treatment in a mouse model of lung infection using strain PAO1 and its hypermutable derivative PAO⌬mutS are investigated. Groups of 30 mice were treated for 3 days with humanized regimens of ciprofloxacin (CIP), tobramycin (TOB), CIP plus TOB, or placebo, and mortality, total lung bacter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
80
1
2

Year Published

2007
2007
2013
2013

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(89 citation statements)
references
References 49 publications
6
80
1
2
Order By: Relevance
“…The breakpoint used for MexAB-OprM hyperproduction was a threefold higher level of expression than that by PAO1. Previously obtained or constructed PAO1 mutants that hyperproduce AmpC or the several efflux pumps were used as controls in the RT-PCR experiments (18,21,23 …”
Section: Quantification Of Gene Expression By Rt-pcrmentioning
confidence: 99%
“…The breakpoint used for MexAB-OprM hyperproduction was a threefold higher level of expression than that by PAO1. Previously obtained or constructed PAO1 mutants that hyperproduce AmpC or the several efflux pumps were used as controls in the RT-PCR experiments (18,21,23 …”
Section: Quantification Of Gene Expression By Rt-pcrmentioning
confidence: 99%
“…The presence of hypermutable strains has been found to be linked to the high antibioticresistance rates of P. aeruginosa clinical isolates recovered from patients with chronic lung infections (1,9,11,16), and in vitro and in vivo experiments have shown that hypermutation dramatically speeds up resistance development during exposure to antimicrobial agents (1,12). Nevertheless, except for antimicrobial resistance development, a link between hypermutation and the genetic adaptation required for the longterm persistence of chronic infections has not yet been proved.…”
mentioning
confidence: 99%
“…Alhough this is the first time this association has been demonstrated, it is not surprising because both of these phenotypes increase with duration of infection in the CF lung (3,10). The mucoid phenotype is thought to protect bacteria against certain antimicrobials (1, 7), innate immune factors (9), and reactive oxygen species (8), and hypermutators increase the fitness of a bacterial population undergoing stress and increase the likelihood of antimicrobial resistance (11,13,15,17). There may also be an interaction between the two phenotypes; hypermutators undergo mutations at a higher rate and are therefore more likely to acquire a mutation resulting in the mucoid phenotype.…”
mentioning
confidence: 99%
“…Patients with CF commonly harbor hypermutator isolates of this bacterium (3,16), the prevalence of which increases with duration of infection (3), but no other clinical correlates of hypermutator presence have been determined. Hypermutators are more resistant to antimicrobials in vitro (3,11) and in vivo (13) and may increase the fitness of bacterial populations during environmental stress (17).…”
mentioning
confidence: 99%